2018
DOI: 10.1108/jima-06-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Australia’s cognitive, affective and conative destination image: an Emirati tourist perspective

Abstract: Purpose The purpose of this study is to understand the destination image perceptions about Australia – a Western culture country – as held by the rapidly increasing, high spending, culturally dissimilar new segment of travellers, the Emiratis[1] from the United Arab Emirates (UAE). Design/methodology/approach A qualitative methodology was used to understand the cognitive, affective and conative images of Australia. A structured categorisation matrix was used to analyse the data so that only aspects fitting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 76 publications
4
37
0
Order By: Relevance
“…Generally, tourists need a positive image of a destination to consider visiting (Braun et al, 2013; Ramkissoon and Nunkoo, 2011). Finally a third interrelated component of destination image is the conative or behavioural image, which influences and predicts tourists’ behaviour (Michael et al, 2018).…”
Section: The Role Of Familiarity In Shaping Destination Imagementioning
confidence: 99%
“…Generally, tourists need a positive image of a destination to consider visiting (Braun et al, 2013; Ramkissoon and Nunkoo, 2011). Finally a third interrelated component of destination image is the conative or behavioural image, which influences and predicts tourists’ behaviour (Michael et al, 2018).…”
Section: The Role Of Familiarity In Shaping Destination Imagementioning
confidence: 99%
“…Stepchenkova & Mills's (2010) study revealed that the conative component is linked to revisiting, recommending or saying positive word of mouth based on the positive tourists' expressions. Michael et al (2018) used a qualitative method to understand the cognitive, affective and conative images of Australia. From the affective perspective, Australia is found to be pleasant, family oriented, a fun place, laid back and the local people friendly.…”
Section: Stereotype Content Model (Scm)mentioning
confidence: 99%
“…Understanding the core concept of destination image has attained immense attention by practitioners and academicians in last few years. Analysis of destination image from different perspectives has contributed to a great understanding as how the destination image is formed; the importance/performance of information sources; the implications of personal factors and motivations; the impact of tourists' experience and familiarity with destination and/or with similar type of holiday making (Russel & Pratt, 1980;Fayeke & Crompton, 1991;Gartner, 1993;Echtner & Richie, 1993;Baloglu & McClearly, 1999;Baloglu, 2001;Baloglu & Mangaloglu, 2001;Beerli & Martin, 2004a, 2004bPike & Ryan, 2004;Agapito et al, 2013;Stylidis et al, 2017;Stylos et al, 2016Stylos et al, , 2017Michael et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars agree on the importance of studying the dimensions of destination image one by one, in order to better understand the complexity of the whole. Michael et al (2018) emphasize that utilizing all three components provides a more nuanced understanding of interrelated contributors of destination image. The three dimensional model of destination image proposed by Gartner (1993), is also supported by Social Psychologists' three dimensions of attitude: cognitive, affective and conative (Allport, 1935;Hilgard, 1980;Aranson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation